Genome structure and molecular phylogeny of the only Eurasian Boechera species, Boechera falcata (Brassicaceae) - Zilov, Danil; Mandáková, Terezie; Popova, Marina; Lysak, Martin A; Windham, Michael D; Brukhin, Vladimir (G3 (Bethesda, Md.), 2025)
Boechera falcata (Turcz.) Al-Shehbaz, previously known as Arabis turczaninowii Ledeb., is a herbaceous perennial of the East Siberian, boreal-steppe ecotype. It is the sole species of the diverse genus Boechera found on the Eurasian continent, with all other species endemic to North America and Greenland. Likely migrating from North America to Eastern Siberia via the Bering Land Bridge during the Pleistocene glaciation, B. falcata presents a unique case for genomic study. The genus Boechera is notable for its many allodiploid and triploid apomicts, which have arisen through complex hybridization of sexual species and ecotypes. To date, only the genomes of 2 American Boechera species, B. stricta and B. retrofracta, have been sequenced and analyzed. In this study, we sequenced, assembled to the chromosome level, and analyzed the highly homozygous 189.36 Mb genome of B. falcata (2n = 14). Molecular phylogenetic analysis of nuclear and organelle genomes revealed a high degree of relatedness to North American relatives. Cytogenetic analysis identified all 22 genomic blocks of crucifers, showing that 5 of the 7 B. falcata chromosomes are collinear with their ancestral counterparts, while 2 have undergone inversions. Allelic analysis of the apomixis marker APOLLO gene revealed that B. falcata contains only sex alleles. The availability of the B. falcata genome will advance studies of the evolution and phylogeny of Brassicaceae species and the mechanisms of apomixis, providing a crucial resource for future research in plant genetics and breeding.
Keywords: Genome, Plant; comparative chromosome painting; chromosome-level genome assembly and annotation; chloroplast genome; genomika; Boechera falcata; chromosome rearrangements; molecular phylogeny; chromozomy rostlin; genome structure; Genomics; Phylogeny; genom rostlinný; Chromosomes, Plant; fylogeneze; Brassicaceae